PENGARUH PENDEKATAN SAINTIFIK TERHADAP KEMAMPUAN BAHASA ANAK USIA 5-6 TAHUN DI TK GRACIA SUSTAIN MEDAN KOTA : THE INFLUENCE OF A SCIENTIFIC APPROACH ON THE LANGUAGE ABILITIES OF CHILDREN AGED 5-6 YEARS AT GRACIA SUSTAIN MEDAN CITY KINDERGARTEN - Prita Anjeli Br Tarigan; Juli Yanti Harahap (incrementapedia, 2023)
The scientific approach is learning that is designed in such a way that students actively develop competencies, attitudes, knowledge and skills through the stages of observing, asking, collecting information, reasoning and communicating it. The problem with this research is that children's language skills are still underdeveloped. This research aims to determine the effect of a scientific approach on the language abilities of children aged 5-6 years at Gracia Sustain Kindergarten Medan City TA 2022/2023. This type of research is a type of quantitative research (experiment) with a pre-experimental research design that looks for relationships between two or more variables. The approach used in this research is one-group pre-test and post-test design, namely a type of research using cause and effect relationships involving one group of subjects. The population of this study were children aged 5-6 years (group B) at Kindergarten Gracia Sustain Medan City TA 2022/2023. The results of the research show that there is an influence of the scientific approach on the language skills of children aged 5-6 years at Gracia Sustain Kindergarten Medan City FY 2022/2023. This can be proven from the results of hypothesis calculations, based on calculations obtained from the post-test, the data normality test results carried out state that the data is normally distributed and the t-test is above the tcount>ttable value or 4.1724>1.734, then Ho is rejected and Ha is accepted. , so it can be stated that there is a significant influence of the scientific approach on the language skills of children aged 5-6 years at Gracia Sustain Kindergarten Medan City TA 2022/2023.